2013
DOI: 10.1038/ncomms2492
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage-based signal amplification of RNA

Abstract: RNA detection has become an integral part of current biomedical research. Up to now, the reverse transcription-PCR has been the most practical method to detect mRNA targets. However, RNA detection by reverse transcription-PCR requires sophisticated equipment and it is highly sensitive to contamination with genomic DNA. Here we report a new isothermal reaction to simultaneously amplify and detect RNA, based on cleavage by DNAzyme and signal amplification. Cleavage-based signal amplification of RNA cannot be con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 38 publications
2
56
0
1
Order By: Relevance
“…RT-qPCR remains the gold standard for RNA quantification; however, this technique is limited by time and equipment constraints and can be prone to contamination. To minimize these limitations, isothermal RNA amplification techniques have been developed [7][8][9][10][11][12][13][14], but these still remain dependent on nucleic acid replication and are therefore hindered by polymerase speed and fidelity. Recent RNA detection methods that have employed duplex specific nuclease (DSN) isolated from the Paralithodes camtschaticus crab [15,16], remain limited to microRNA [17] and are thus unsuitable for longer RNA templates like virus genomic or mRNA targets.…”
Section: Introductionmentioning
confidence: 99%
“…RT-qPCR remains the gold standard for RNA quantification; however, this technique is limited by time and equipment constraints and can be prone to contamination. To minimize these limitations, isothermal RNA amplification techniques have been developed [7][8][9][10][11][12][13][14], but these still remain dependent on nucleic acid replication and are therefore hindered by polymerase speed and fidelity. Recent RNA detection methods that have employed duplex specific nuclease (DSN) isolated from the Paralithodes camtschaticus crab [15,16], remain limited to microRNA [17] and are thus unsuitable for longer RNA templates like virus genomic or mRNA targets.…”
Section: Introductionmentioning
confidence: 99%
“…The extraordinary stability of miRNAs in circulating blood is due to the fact that circulating miRNAs are mainly incorporated into exosomes, microvesicles, and apoptotic bodies as well as they form stable complexes with RNA-binding proteins and HDL lipoprotein (11,13,19). After miRNA biomarkers were indicated as potential biomarkers for cardiovascular diseases, enormous efforts have been made to improve the detection technologies and quantification has become readily accessible (21)(22)(23). Therefore, the accurate, rapid, convenient and inexpensive analytic instruments to detect miRNA may be used in clinical practice in the near future.…”
Section: Mirnas As Biomarkers Of Amimentioning
confidence: 99%
“…However, there are few examples of PCR amplification using RNA primer. In our previous work, we found that the mismatch at the 3-end of the RNA primer could inhibit the extension of mesophilic DNA polymerase on the DNA template [6], while the DNA primer could not. Also, the RNA/DNA hybrid is more stable, and has better specificity than DNA/DNA hybrid in vitro [7].…”
Section: Introductionmentioning
confidence: 99%